Effect of Phytohormones on Rooting of Nodal Shoot Cuttings of Grewia optiva Drummond - Husen, Azamal; Khali, Rakesh; Nautiyal, S.; Bhandari, H. C. S. (Indian Forester, 2003)
The rooting response of nodal shoot cuttings of Grewia optiva Drummond, as influenced two phytohormones, namely, indole-3-butyrie-acid (Lea) and Î±-napthalenp Acetic Acid (NAA) applied in three conecntrations (1000 to 3000 ppm) were examined under intermittent mist in vermiculite culture. Assessments on rooting, sprouting as well as on root number and their length on the cuttings were conducted after 25-days of treatments. The highest per cent rooting (75.56%) and sprouting (73.76%) was obtained from untreated cuttings. NAA 3000 ppm treated cuttings showed the lowest per cent rooting 08.89%) and sprouting 05.80%) compared to IRA treatments. However, positive response was observed in root numbers and their length by the application of IRA and NAA. The possibilities of use nodal of shoot cuttings for raising clonal material of G. optiva, an excellent fodder tree species of mountain regions have been discussed.